The International Long‐Term Ecological Research–East Asia–Pacific Regional Network (ILTER‐EAP): history, development, and perspectives. Issue 1 (26th December 2017) - Kim, Eun‐Shik; Trisurat, Yongyut; Muraoka, Hiroyuki; Shibata, Hideaki; Amoroso, Victor; Boldgiv, Bazartseren; Hoshizaki, Kazuhiko; Kassim, Abd Rahman; Kim, Young‐Sun; Nguyen, Hong Quan; Ohte, Nobuhito; Ong, Perry S.; et al.
Abstract: There are growing needs to broaden and deepen our multi‐faceted understanding of the ecosystems, and the networks of Long‐Term Ecological Research (LTER) can play significant roles in fostering and applying ecosystem studies at regional and global scales. The International LTER Network (ILTER) is organized as a global network of field research sites and scientists to address current ecological issues such as biodiversity loss and ecosystem degradation within a globally changing environment. The ILTER East Asia–Pacific Regional Network (ILTER‐EAP) is one of the four constituent ILTER regional networks. Since 1995, ILTER‐EAP has been developed to promote data sharing, research collaborations and capability building in the science and to bridge gaps between societal needs and scientific imperatives on concerns in the Asia–Pacific Region. Currently, ILTER‐EAP comprises nine formal ILTER members and two associate networks. Their activities involve long‐term and multiple‐site observations of structural, functional and developmental aspects of ecosystems, data sharing, and bridging society and ecological science. This paper presents a review of the activities of ILTER‐EAP, focusing on its: (1) vision and the development following its inception, (2) scientific activities and major outputs related to selected thematic areas, (3) contributions from ILTER‐EAP to the international initiatives, and (4) future challenges and opportunities relating to its development and role in facilitating regional and global research collaborations. Accordingly, regional research questions were identified that could be most effectively addressed by opening up a common research platform, integrated data management system and the network science, which is open to all interested parties.